Circular RNAs and Their Emerging Roles in Immune Regulation - Yang, Lan; Fu, Jinrong; Zhou, Yufeng (Frontiers in Immunology, 2018)
Circular ribonucleic acid (RNA) molecules (circRNAs) are covalently closed loop RNA molecules with no 5′ end caps or 3' poly (A) tails, which are generated by back-splicing. Originally, circRNAs were considered to be byproducts of aberrant splicing. However, in recent years, development of high-throughput sequencing has led to gradual recognition of functional circRNAs, and increasing numbers of studies have elucidated their roles in cancer, neurologic diseases, and cardiovascular disorders. Nevertheless, studies of the functions of circRNAs in the immune system are relatively scarce. In this review, we detail relevant research on the biogenesis and classification of circRNAs, describe their functional mechanisms and approaches to their investigation, and summarize recent studies of circRNA function in the immune system.